Effect of an electricity voucher on electricity use. (November 2019) - Viggers, Helen; Keall, Michael; Howden-Chapman, Philippa; Wickens, Kristin; Ingham, Tristram; Davies, Cheryl; Chapman, Ralph; Crane, Julian
Abstract: The aim of this paper is to examine the effect of receiving a voucher for electricity on the electricity use of a household. The Warm Homes for Elder New Zealanders Study was a randomised controlled trial which gave participants aged over 55 with chronic obstructive pulmonary disease a voucher providing NZ500 credit to their electricity account for one winter. Electricity use increased over the winter the participant received the voucher. Participants with lower initial electricity use increased their consumption by about 10%, those with medium- or high-initial use by 2–3%. However, most participants did not use the entire value of the voucher on additional electricity. The study involved only a small informational component: this consisted of a brochure sent to the participants to encourage them to increase their energy use. This was designed to mimic the effects of a possible widespread rollout of this programme. The policy implication of this analysis is that a winter energy voucher accompanied by minimal education was effective at increasing winter energy use among a vulnerable sub-population with a health condition that merited additional heating in winter. Highlights: Older people who received an electricity voucher used more electricity. Greatest difference in energy use was among the low users. Clear labelling of electricity vouchers for warmth increased electricity usage.